Sounds of a changing sea: Temperature drives acoustic output by dominant biological sound-producers in shallow water habitats - Lillis, Ashlee; Mooney, T. Aran (Frontiers in Marine Science, 2022)
The ocean’s soundscape is fundamental to marine ecosystems, not only as a source of sensory information critical to many ecological processes but also as an indicator of biodiversity and habitat health. Yet, little is known about how ecoacoustic activity in marine habitats is altered by environmental changes such as temperature. The sounds produced by dense colonies of snapping shrimp dominate temperate and tropical coastal soundscapes worldwide and are a major driver broadband sound pressure level (SPL) patterns. Field recordings of soundscape patterns from the range limit of a snapping shrimp distribution showed that rates of snap production and associated SPL were closely positively correlated to water temperature. Snap rates changed by 15-60% per °C change in regional temperature, accompanied by fluctuations in SPL between 1-2 dB per °C. To test if this relationship was due to a direct effect of temperature, we measured snap rates in controlled experiments using two snapping shrimp species dominant in the Western Atlantic Ocean and Gulf of Mexico (Alpheus heterochaelis and A. angulosus). Snap rates were measured for shrimp held at different temperatures (across 10-30 °C range, with upper limit 2°C above current summer mean temperatures) and under different social groupings. Temperature had a significant effect on shrimp snap rates for all social contexts tested (individuals, pairs, and groups). For individuals and shrimp groups, snap production more than doubled between mid-range (20°C) and high (30°C) temperature treatments. Given that snapping shrimp sounds dominate the soundscapes of diverse habitats, including coral reefs, rocky bottoms, seagrass, and oyster beds, the strong influence of temperature on their activity will potentially alter soundscape patterns broadly. Increases in ambient sound levels driven by elevated water temperatures has ecological implications for signal detection, communication, and navigation in key coastal ecosystems for a wide range of organisms, including humans.